Pengaruh Komunikasi Kerja , Kepemimpinan dan Pelatihan kerja terhadap Kepuasan Kerja karyawan PT. Sepatu Bata - Juanda Situmorang; Yuli Rama Dewi; Monarisa Ritiani Br Ginting; Rafida Khairani (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2022)
This study aims to determine the effect of work communication on job satisfaction of employees of PT. Sepatu Bata, knowing the influence of leadership on job satisfaction of employees of PT. Sepatu Bata, knowing the effect of job training on job satisfaction of employees of PT Sepatu Bata and knowing the effect of work communication, leadership and job training simultaneously on job satisfaction of employees of PT Sepatu Bata is implemented at PT Sepatu Bata with a population of all 25 employees of PT Sepaatu Bata. By using total sampling, this research sample obtained 25 people. The results of the research partially obtained the tcount of work communication (X1) was 3.043 and the t table value was 2.059 provided that the value of tcount> t table (3.043> 2.059) and the value of sig <0.06 (0.000 <0.05), the value of tcount of leadership ( X2) is 2.720 and the t-table value is 2.059 provided that the tcount> ttable (2.720> 2.059) and the sig value <0.05 (0.013 <0.05), the tcount value for job training (X3) is 3.720 and the t table value is 2.059 with provisions for the value of tcount> ttable (3.207> 2.059) and the value of sig <0.05 (0.004 <0.05), the simultaneous effect of the Fcount value of work communication (X1), leadership (X2) and job training (X3) is 39.728 and the value t table is 2.758 with the provision that the value of Fcount> Ftable (39.728> 2.758) and the sig value <0.05 (0.000 <0.05. The Adjusted RSquare value is 0.829 or adjusted R2 x 100% of 82.90%, meaning that the independent research variable is in the form of Work communication, leadership and job training contribute ih great in explaining the job satisfaction of 82.90% while the remaining 17.10% is influenced by other factors outside the research. The conclusion of the study is partially job communication has a significant effect on job satisfaction, leadership has a significant effect on job satisfaction, job training has a significant effect and is a dominant variable that affects job satisfaction and simultaneously job communication, leadership and job training have a significant effect on job satisfaction. Keywords : job communication, leadership, job training, job satisfaction